Beyond Crizotinib: A Systematic Review and Meta-Analysis of the Next-Generation ALK Inhibitors as First-Line Treatment for ALK-Translocated Lung Cancer - Giunta, Emilio Francesco; Signori, Alessio; West, Howard Jack; Metro, Giulio; Friedlaender, Alex; Parikh, Kaushal; Banna, Giuseppe Luigi; Addeo, Alfredo (Frontiers in Oncology, 2022)
Background. Second and third generation ALK inhibitors (ALKIs) have been recently approved for ALK-translocated lung cancer treatment, improving - and expanding - the first-line scenario. Methods. In this systematic review and metanalysis, we investigated the efficacy and safety of next-generation ALKIs in untreated advanced ALK-translocated lung cancer patients, searching for randomized phase III controlled trials through in databases (PubMed, EMBASE, and the Cochrane Library). Inclusion and exclusion of studies, assessment of quality, data extraction, and synthesis were independently accomplished by two reviewers, with discrepancies adjudicated by a third reviewer. Stata (StataCorp., v.16) software was used for the metanalysis. Results. In total, seven randomized controlled trials met our inclusion criteria. Comparing the results of next-generation ALKIs and control therapy (crizotinib or chemotherapy), next-generation ALKIs significantly improved progression free survival (PFS), overall survival (OS), objective response rate (ORR), disease control rate (DCR), any lesion (aCNSRR) and measurable lesions of central nervous system response rate (mCNSRR). Safety results were similar between experimental and control groups. Conclusion. Next-generation ALKIs should be considered the treatment of choice for the first-line of ALK-translocated lung cancer based on the overall efficacy superiority, including OS, PFS, ORR and CNS disease control without increased toxicity over crizotinib or chemotherapy confirmed by this analysis. In the absence of head-to-head data, choosing between these molecules should be guided by physician experience and preference, drug-specific safety profiles, schedule.